Propaganda Buzzer Politik pada Pemilihan Presiden 2024 - Muhamad Husein; Syahrial Syarbaini (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2024)
This research aims to identify how buzzer propaganda is used to manipulate public opinion and create a political image favorable to certain presidential candidates, as well as its impact on political ethics and social dynamics. This research uses a qualitative approach with a constructivist paradigm to explore the activities of political buzzers on social media. The methods used include in-depth interviews with expert informants, and literature studies. Data was analyzed using to identify patterns, themes, and persuasive techniques used by buzzers in shaping public opinion. The results showed that propaganda and imagery became the key to success in the presidential election campaign, with buzzers playing a central role in framing the media to support candidate pairs. The transformation of the buzzer function from a business tool to a political tool has a major impact on social and political dynamics, often through the spread of slander and issues that trigger social tensions.